2022
DOI: 10.3390/agriculture12060874
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils in Broiler Chicken Production, Immunity and Meat Quality: Review of Thymus vulgaris, Origanum vulgare, and Rosmarinus officinalis

Abstract: The use of essential oils in animal nutrition has attracted attention as a potential substitute for antibiotic growth promoters in the past twenty-five years. This paper will review the current scientific evidence on the usage of essential oils from Lamiaceae family members such as Thymus vulgaris (thyme), Origanum vulgare (oregano), and Rosmarinus officinalis (rosemary) in broiler nutrition in terms of production results, immunity, and meat quality properties. Essential oils are effective in broiler nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 173 publications
0
24
0
Order By: Relevance
“…It was found that the use of different combinations of additives (such as medium-chain fatty acids, short-chain fatty acids, oregano essential oil, and sweet basil essential oil) exhibited positive effects on the growth performance of broilers [ 1 ]. Extracts of medicinal herbs (aromatic herbs) have received increasing attention from both researchers and producers as potential alternatives to conventional antibiotic growth promoters in broiler rations [ 2 ]. The beneficial effects of these essential oils as well as plant oils are related to their suitable chemical properties and functional groups, whose mechanisms of action remain to be explained [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the use of different combinations of additives (such as medium-chain fatty acids, short-chain fatty acids, oregano essential oil, and sweet basil essential oil) exhibited positive effects on the growth performance of broilers [ 1 ]. Extracts of medicinal herbs (aromatic herbs) have received increasing attention from both researchers and producers as potential alternatives to conventional antibiotic growth promoters in broiler rations [ 2 ]. The beneficial effects of these essential oils as well as plant oils are related to their suitable chemical properties and functional groups, whose mechanisms of action remain to be explained [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically active components of essential oils of thyme, oregano, and rosemary stimulate the activity of beneficial bacteria, thus contributing to the balance of microflora, that is, they are an effective prerequisite for protection against pathogenic microorganisms (Abdel-Fattah et al, 2008;Puvača et al, 2022). Increasing the number of beneficial bacteria not only reduces the number of available substrates for pathogens, but also stabilises the pH of the intestine, ensuring optimal activity of pancreatic enzymes, which further leads to improved nutrient absorption and, accordingly, improved productive characteristics (Jakubowska & Karamucki, 2021;Puvača et al, 2022). There are also data on the anticoccidial activity of thyme and rosemary essential oils on the body of chickens (Lahlou et al, 2021).…”
Section: Economic Indicatorsmentioning
confidence: 99%
“…Influence of Plant Biological Additive on the Productivity of Young RabbitsScientific Horizons, 2022, Vol 25,No. 10.…”
mentioning
confidence: 99%
“…The most common type of terpenoids in EOs is monoterpenes, which can make up as much as 90% of the total and have a very soothing, subtle aroma. A monoterpene consists of two isoprene units, or 10 carbon atoms (Puvača et al 2022). Numerous terpene synthases monitor the synthesis of monoterpenes.…”
Section: Citrus Aurantifoliamentioning
confidence: 99%
“…EOs from various plant species can include anywhere from 20 to 60 different biologically active compounds, with only a subset (20-70%) playing a significant role and the rest present only in minute quantities. It is possible for there to be a big difference in the amount of biologically active substances present depending on the plant parts utilized, the season they were collected, and the region they were cultivated (Hoffmann 2020;Puvača et al 2022).…”
Section: Citrus Aurantifoliamentioning
confidence: 99%